Assessing severe acute respiratory syndrome coronavirus 2 infectivity by reverse‐transcription polymerase chain reaction: A systematic review and meta‐analysis. (2nd April 2022) - Fomenko, Alexey; Weibel, Stephanie; Moezi, Helia; Menger, Kristina; Schmucker, Christine; Metzendorf, Maria‐Inti; Motschall, Edith; Falcone, Valeria; Huzly, Daniela; Panning, Marcus; Rücker, Gerta; Hengel, Hartmut
Abstract: The cornerstone of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) detection is reverse‐transcription polymerase chain reaction (RT‐PCR) of viral RNA. As a surrogate assay SARS‐CoV‐2 RNA detection does not necessarily imply infectivity. Only virus isolation in permissive cell culture systems can indicate infectivity. Here, we review the evidence on RT‐PCR performance in detecting infectious SARS‐CoV‐2. We searched for any studies that used RT‐PCR and cell culture to determine infectious SARS‐CoV‐2 in respiratory samples. We assessed (i) diagnostic accuracy of RT‐PCR compared to cell culture as reference test, (ii) performed meta‐analysis of positive predictive values (PPV) and (iii) determined the virus isolation probabilities depending on cycle threshold (Ct) or log10 genome copies/ml using logistic regression. We included 55 studies. There is substantial statistical and clinical heterogeneity. Seven studies were included for diagnostic accuracy. Sensitivity ranged from 90% to 99% and specificity from 29% to 92%. In meta‐analysis, the PPVs varied across subgroups with different sampling times after symptom onset, with 1% (95% confidence interval [CI], 0%–7%) in sampling beyond 10 days and 27% (CI, 19%–36%) to 46% (CI, 33%–60%) in subgroups that also included earlier samples. Estimates of virus isolation probability varied between 6% (CI, 0%–100%) and 50% (CI, 0%–100%) at a Ct value of 30 and between 0% (CI, 0%–22%) and 63% (CI, 0%–100%) at 5 log10 genome copies/ml. Evidence on RT‐PCR performance in detecting infectious SARS‐CoV‐2 in respiratory samples was limited. Major limitations were heterogeneity and poor reporting. RT‐PCR and cell culture protocols need further standardisation.